1989
DOI: 10.2466/pms.1989.69.1.349
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Processing and the Retention of Paired-Associates

Abstract: The effect of self-reference, semantic, and rote processing on the retention of paired-associates was examined at intervals of 5 min. and 2 wk. 25 subjects per group were given 120 sec. to process each of 15 paired-associates by self-reference, semantic, or rote. The pairs were a low meaningful nonsense word and a high meaningful English noun. At both retention intervals, self-reference and semantic processing produced significantly higher retention than rote processing and there was no difference in retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…There was no interaction between the two experimental factors of material and instruction. Thus, it seems that the instruction in itself is sufficient to produce the effect regard-less of whether the material carried any explicit semantic content consistent with the findings of Vochatzer and Blick (1989). Our findings indicate that the explicit instruction promotes a mode of processing that favors retention regardless of whether there is explicit semantic content to associate with preexistent knowledge or experience.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…There was no interaction between the two experimental factors of material and instruction. Thus, it seems that the instruction in itself is sufficient to produce the effect regard-less of whether the material carried any explicit semantic content consistent with the findings of Vochatzer and Blick (1989). Our findings indicate that the explicit instruction promotes a mode of processing that favors retention regardless of whether there is explicit semantic content to associate with preexistent knowledge or experience.…”
Section: Discussionsupporting
confidence: 79%
“…In previous behavioral studies, the LOP effect has commonly been investigated using language-based material, and in particular, Vochatzer and Blick (1989) investigated the LOP effect using words and pseudo-words. Their results indicated that the LOP effect in the pseudo-word condition was comparable to the effect observed in the word condition (Vochatzer and Blick, 1989). The primary objective of the behavioral study was to establish the LOP effect in our experimental setting using two visual materials (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, "shallow" cognitive processing (e.g., determining how many letters are in a parCopyright 2000 Psychonomic Society, Inc. 158 ticular word or determining whether the word has any vowels) will lead to poorer memory performance. Many studies have since supported this idea that deeper processing of presented items leads to greater retention (Craik & Tulving, 1975;Fisher & Craik, 1977, 1980Flannagan & Blick, 1989;Toth, 1996;Vochatzer & Blick, 1989). Hence, the concept has come to be regarded as one of the most well-established information processing theories of the past 20 years (Lockhart & Craik, 1990).…”
mentioning
confidence: 99%